Customer Satisfaction as an Intervening Variable in the Relationship Between Service Quality, Marketing Mix, and Customer Trust at Airports - Lestiani, Melia Eka; Budiono, Cyrilus Sukaca; Jannah, Tsamratul; Poerwanto, Eko; Mardwianta, Benedictus (Vortex, 2025)
An airport is a facility where all stakeholders in the aviation industry converge, and its core product is “service,” which includes services for passengers, cargo, and aircraft. Customer satisfaction at airports is an essential outcome that must be delivered to all aviation industry stakeholders. This study aims to analyze the influence of service quality and marketing mix on customer trust, with customer satisfaction serving as an intervening variable at the airport. In reality, many airport service users still feel dissatisfied with both the services provided and the existing facilities. This is evident from various complaints submitted by users, indicating that they have not yet experienced satisfactory airport services. This research employs a quantitative method by distributing questionnaires to 100 respondents, consisting of domestic passengers at Minangkabau International Airport. The findings reveal that service quality and marketing mix have a significant partial and simultaneous effect on customer satisfaction. Furthermore, service quality, marketing mix, and customer satisfaction—both partially and simultaneously—have a significant influence on customer trust. However, the customer satisfaction variable is unable to mediate the relationship between service quality and the marketing mix toward customer trust.